Automation of measurements on the state standard of the unit of phase shift angle between two voltages - Velychko, Oleh; Kulish, Yuliia (Видавництво Львівської політехніки, 2023)
The phase is one of the main parameters of the oscillatory process in electric circuits and contains two components – constant and variable. More often, it is not the actual phase that is measured, but the phase shift angle (PSA) between two oscillating processes (voltages or currents) of the same frequency in the range from 0 to 360˚. Then the PSA is equal to the difference between the constant components of the phases of the two oscillations and does not depend on the start of the time count. Most of the modern methods of measuring the phase and PSA are based on the methods of discretization and digital signal processing – complex Fourier transform, least squares, etc. There are many varieties and improvements of these methods, which have different characteristics of measurement accuracy. The LabVIEW graphical programming environment has already become a general- purpose programming environment. Advantages of LabVIEW include simple networking, implementation of common communication protocols, powerful toolkits for process control and data fitting, fast and simple user interface design, and an efficient code execution environment. The article presents the results of the automation of measurements on the State Standard of the PSA between two voltages in the frequency range from 5 Hz to 10 MHz. Automation of precision measurements of PSA using the LabVIEW software environment provides advantages in comparison with manual measurements, in particular, reducing the time of measurement and processing of its results by at least three times. This ensures an increase in the productivity of metrological works; increasing their efficiency and quality, and the possibility of increasing the number of measurements (up to 1000), which allows for improve the root mean square deviation of not less than one and a half times, and reduce the overall standard measurement uncertainty, respectively.
Keywords: Phase shift angle; Voltage; Phase measurements; Measurement standard; Automation